1996
DOI: 10.1007/bf01718301
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of equine herpesvirus 1 glycoprotein D in mammalian cell lines

Abstract: Equine herpesvirus 1 glycoprotein D (EHV-1 gD) expressed constitutively in mammalian cell lines had similar electrophoretic mobility to gD produced in EHV-1 infected cells but lacked a possibly complexed higher molecular weight form seen in the latter. Recombinant gD was N-terminally cleaved at the same site as gD in EHV-1 infected cells and expression was associated with enhanced levels of cell-cell fusion, indicating a role for EHV-1 gD in cell-to-cell transmission of virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Such approach has already been reported for canine influenza, equine influenza virus, West Nile virus and bovine viral diarrhea virus, where virulence genes of these viruses were inserted into an equine herpesvirus type 1 (EHV1) vaccine [142-145]. The rationale behind the insertion of MYXV immunogenic genes into an equine pathogen is based on the fact that EHV1 grows extremely well in rabbit cells and hence, rabbit kidney (RK13) are the most commonly used in vitro cell line to grow EHV1 [146,147]. Still, despite this efficient growth in vitro, it needs to be determined whether EHV1 is capable of inducing robust immune responses in rabbits in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Such approach has already been reported for canine influenza, equine influenza virus, West Nile virus and bovine viral diarrhea virus, where virulence genes of these viruses were inserted into an equine herpesvirus type 1 (EHV1) vaccine [142-145]. The rationale behind the insertion of MYXV immunogenic genes into an equine pathogen is based on the fact that EHV1 grows extremely well in rabbit cells and hence, rabbit kidney (RK13) are the most commonly used in vitro cell line to grow EHV1 [146,147]. Still, despite this efficient growth in vitro, it needs to be determined whether EHV1 is capable of inducing robust immune responses in rabbits in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, alignment of HSV-1 gD sequences indicates the conservation of certain continuous amino acid segments that could provide shared immunogenic responses. In addition, on the basis of the overall structure conservation of EHV-1 and HSV-1 gDs (21,22), certain conformational epitopes may be conserved and may contribute to the observed cross-neutralizing activity of VC2. Also, it is likely that a number of other viral proteins may contribute immunogenic determinants that are common to strains and that produce cross-neutralizing activity.…”
Section: Figmentioning
confidence: 99%
“…Unlike in other α-herpesviruses, ectopically expressed gD EHV−1 is retained in the Golgi complex, which is associated with the secondary envelopment process (34). Although a previous study showed that gD EHV−1 was detected on the cell membrane of CHO and RK13 cells, very weak uorescence on the cell membrane and strong signals in the cytoplasm were detected, also indirectly proving the Golgi retention phenotype of gD EHV−1 (51) . The present study demonstrated that gD EHV−1 Golgi retention might be achieved by inhibiting vesicle formation, which is mainly regulated by its TM-CT domain.…”
Section: Discussionmentioning
confidence: 82%